2019
DOI: 10.1080/0284186x.2019.1582800
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic position, referral and attendance to rehabilitation after a cancer diagnosis: A population-based study in Copenhagen, Denmark 2010–2015

Abstract: Background: Implementation of new cancer services may lead to socioeconomic differences in uptake and despite reports of more unmet needs among patients with low socioeconomic position studies have found that these patients receive less rehabilitation. We aimed to investigate associations between indicators for socioeconomic position and referral as well as attendance to rehabilitation for cancer. Methods: Through the Danish Cancer Registry, we identified all persons diagnosed with cancer in Copenhagen municip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The index is based on data from administrative, population-based registries with the future intention to study whether and when during the disease trajectory socially vulnerable patients with advanced cancer use rehabilitation and palliative care services. As these services are regarded as essential aspects of high-quality cancer care [12], and with indications of social inequality in access to these services [13][14][15], more knowledge is needed on how to reach socially vulnerable cancer patients regarding rehabilitation and palliative care [16]. The development of the rSVI is one step in the attempt to ensure optimal cancer treatment for all Danish cancer patients regardless of social position and vulnerability, as described by Danish Research Center for Equality in Cancer (COMPAS) [17].…”
Section: Introductionmentioning
confidence: 99%
“…The index is based on data from administrative, population-based registries with the future intention to study whether and when during the disease trajectory socially vulnerable patients with advanced cancer use rehabilitation and palliative care services. As these services are regarded as essential aspects of high-quality cancer care [12], and with indications of social inequality in access to these services [13][14][15], more knowledge is needed on how to reach socially vulnerable cancer patients regarding rehabilitation and palliative care [16]. The development of the rSVI is one step in the attempt to ensure optimal cancer treatment for all Danish cancer patients regardless of social position and vulnerability, as described by Danish Research Center for Equality in Cancer (COMPAS) [17].…”
Section: Introductionmentioning
confidence: 99%
“…1–3 Despite a tax-funded and needs-based organisation of the Danish health system, and hence largely free access to healthcare for all, social inequality in cancer care has been noted repeatedly in Denmark, 4–10 including in cancer rehabilitation and palliative care. 1115…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Despite a tax-funded and needsbased organisation of the Danish health system, and hence largely free access to healthcare for all, social inequality in cancer care has been noted repeatedly in Denmark, [4][5][6][7][8][9][10] including in cancer rehabilitation and palliative care. [11][12][13][14][15] In Denmark, cancer care is governed by a standardised 'cancer package', which includes patients' referral by their general practitioner to hospital for diagnosis, treatment in in-patient and outpatient hospital settings and oncologist's assessment of patient needs and possible referral to community-based rehabilitation and palliative care. 16 Despite this standardised referral pathway embedded in the cancer package, referral to community-based rehabilitation and palliative care is not consistently provided by all hospitals or for all cancer diagnoses.…”
mentioning
confidence: 99%
“…Second, patients living in areas of relative disadvantage, particularly areas at distance from oncology centers, may be substantially sicker before seeing their provider. Alternatively, oncologists' likelihood of intervening for a given level of symptoms may depend on patient factors including socioeconomic status, race, or ethnicity 50–56 . For example, Check et al 55 found both racial and socioeconomic disparities in the use of aprepitant for CINV prevention among women with breast cancer.…”
Section: Discussionmentioning
confidence: 99%